Modified Lithium-Ion Battery Cathode Material, Its Preparation Method and Application
Modifying the lithium-ion positive electrode material by doping and coating carbon, the purity and stability of Li5FeO4 material is solved, the electrochemical activity and battery performance are improved, and the preparation process is simplified.
Patent Information
- Application Number
- CN202210269254.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-18
- Publication Date
- 2025-07-04
- Estimated Expiration
- 2042-03-18
AI Technical Summary
The existing Li5FeO4 positive electrode materials have low purity, large particle size differences, non-conductive and unstable air, and complex preparation process, affecting electrochemical activity and industrial production.
Agglomerated agglomerate modified lithium ion positive electrode material is used to form spherical particles through pulverization and secondary sintering. The carbon is doped in the material and the surface is coated with a carbon layer to block the contact between water and carbon dioxide in the air, thereby improving conductivity and stability.
The conductivity and stability of the material are improved, the charge and discharge specific capacity and the circulation performance of lithium-ion batteries are improved, the material is more stable in the air, and the preparation process is simplified.
Smart Images

Figure CN114709383B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and particularly relates to a modified lithium-ion battery cathode material, a preparation method thereof, and an application thereof. Background Art
[0002] During the charging process of a lithium-ion battery, lithium ions are removed from the cathode and embedded in the anode, and during discharging, lithium ions migrate from the anode to the cathode. However, during the cycling process, a CEI film (surface electrolyte interface film) is formed on the surface of the cathode material and an SEI film (solid electrolyte interface film) is formed on the surface of the anode material. This process results in the consumption of active lithium in the original material, reducing the charge-discharge efficiency. To improve the charge-discharge efficiency, a modified lithium-ion battery material can be added to the cathode or anode. For example, lithium powder and lithium foil are added to the anode material, and high-capacity lithium-containing oxides, including lithium-rich compounds, conversion reaction-based nanocomposites, and binary lithium compounds, etc., are added to the cathode material to solve the irreversible capacity loss caused by the consumption of active lithium. Compared with the high-difficulty and high-investment anode process, adding a modified lithium-ion battery material to the cathode is simple and convenient.
[0003] Among the modified lithium-ion battery cathode materials, Li5FeO4 is a safe and reliable material with relatively low cost. It can release a large amount of lithium ions during the first charging, and the product after releasing lithium ions has extremely low activity and will not undergo re-insertion of lithium or dissolution. It can significantly improve the cycle efficiency and energy density of lithium-ion batteries. Therefore, it is an ideal modified lithium-ion cathode material with great potential. However, common Li5FeO4 has low purity, large particle size differences, and is not conductive itself, seriously affecting the exertion of its electrochemical activity. Moreover, it is unstable in air and needs to be stored and used in an inert atmosphere. And the preparation conditions are generally liquid phase, chemical vapor deposition, or high-temperature long-time solid-phase sintering, and the preparation process is complex and not easy to industrialize. Summary of the Invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. For this purpose, the present invention provides a modified lithium-ion battery cathode material, a preparation method thereof, and an application thereof. The material is an agglomerated modified lithium-ion cathode material doped and coated with carbon, which can block the direct contact between the surface of Li5FeO4 and water and carbon dioxide in the air, eliminating or alleviating the "air-sensitive effect" on the surface of the modified lithium-ion cathode material.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] A modified lithium-ion battery cathode material, whose chemical formula is Li5FeO4@C; the modified lithium-ion battery cathode material is an agglomerate, and the agglomerate is formed by the agglomeration of spherical-like particles.
[0007] The aggregate refers to that the crushed materials in step (1) of the preparation method form small spherical particles after sintering and then grow and agglomerate together to form the aggregate.
[0008] In Li5FeO4@C, part of the carbon is doped into Li5FeO4 and part of the carbon is coated on the surface of Li5FeO4. This is because the carbon source is mixed on the surface of the crushed materials. After the second sintering, the crushed materials grow, and part of it is doped into Li5FeO4 while part of the carbon is coated on the surface of Li5FeO4.
[0009] Preferably, the average particle size of the modified lithium ion cathode material is 1.0 - 10 μm, and the specific surface area is 3.0 - 15.0 m 2 / g.
[0010] Preferably, the particle size of the spherical particles is 10 - 500 nm.
[0011] Preferably, the modified lithium ion cathode material has a charge specific capacity of 645 - 655 mAh / g and a discharge specific capacity of 2.1 - 2.6 mAh / g when charged and discharged at a current density of 0.23C in the charging voltage range of 2.8 - 4.25V.
[0012] Preferably, the mass percentage of carbon in the modified lithium ion cathode material is 1 - 18%.
[0013] A preparation method of a modified lithium ion battery cathode material includes the following steps:
[0014] (1) Mix a lithium source and an iron source, conduct the first sintering, and then crush to obtain crushed materials;
[0015] (2) Mix the crushed materials with a carbon source, conduct the second sintering, crush, and screen to obtain the modified lithium ion battery cathode material; the molar ratio of lithium in the lithium source to iron in the iron source is (5.0 - 6.0):1; the temperature of the second sintering is 450 - 750 °C; the particle size D50 of the crushed materials is 1.0 - 5.0 μm.
[0016] Preferably, in step (1), the lithium source is at least one of lithium hydroxide, lithium carbonate, lithium acetate, lithium borate, lithium metaborate, lithium lactate, lithium nitrate, lithium oxalate, or lithium oxide.
[0017] Preferably, in step (1), the iron source is at least one of ferric nitrate, ferrous nitrate, ferric chloride, ferrous chloride, ferric sulfate, ferrous sulfate, ferric citrate, iron oxide, or magnetite.
[0018] Preferably, in step (1), the molar ratio of lithium in the lithium source to iron in the iron source is (5.0 - 6.0):1.
[0019] Preferably, in step (1), the atmosphere for the first sintering is at least one of oxygen, nitrogen, argon, helium, and neon.
[0020] Preferably, in step (2), the atmosphere for the second sintering is at least one of oxygen, nitrogen, argon, helium, and neon.
[0021] Preferably, in step (1), the heating rate for the first sintering is 1°C - 10°C / min, the temperature for the first sintering is 400 - 750°C, and the time for the first sintering is 4 - 20 h.
[0022] More preferably, the temperature for the first sintering is 400 - 500°C, and the time for the first sintering is 4 - 15 h.
[0023] Preferably, in step (1), the equipment used for the pulverization is one of a jet mill and a mechanical grinder.
[0024] Preferably, in step (2), the carbon source is at least one of polyethylene glycol, polyvinyl alcohol, polyacrylic acid, polypyrrole, fatty alcohol polyoxyethylene, glucose, sucrose, conductive graphite, acetylene black, carbon fiber, Ketjen black, carbon nanotubes, and graphene.
[0025] More preferably, the carbon source is at least one of polyethylene glycol, polyvinyl alcohol, polyacrylic acid, polypyrrole, fatty alcohol polyoxyethylene, glucose, and sucrose.
[0026] Preferably, in step (2), the content of the carbon source is 1 - 25% by mass of the modified lithium-ion cathode material.
[0027] Preferably, in step (2), the heating rate for the second sintering is 1°C - 10°C / min, the temperature for the second sintering is 450 - 750°C, and the time for the second sintering is 4 - 12 h.
[0028] More preferably, the temperature for the second sintering is 450 - 550°C, and the time for the second sintering is 4 - 10 h.
[0029] Preferably, in step (2), the sieving is through a 300-mesh vibrating sieve.
[0030] A battery includes the above-mentioned modified lithium-ion battery cathode material.
[0031] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0032] (1) The present invention prepares an agglomerated modified lithium-ion cathode material doped and coated with carbon (since the particles of the pulverized material are very small, 1.0 - 5.0 μm, and the carbon source is mixed on the surface of the pulverized material. After the second sintering, the pulverized material grows, so part of the carbon is doped into the material and part of the carbon is coated on the surface of the material). The coated carbon can block the direct contact between the surface of Li5FeO4 (modified lithium-ion cathode material) and water and carbon dioxide in the air, eliminate or alleviate the "air-sensitive effect" on the surface of the modified lithium-ion cathode material, and improve the stability of the material in the air; the doped carbon plays a role in conductivity. The secondary particles of the above agglomerates are uniformly sized spherical-like, and the spherical-like particles are relatively small. In the charging voltage range of 2.8 - 4.25 V, with a charge-discharge current density of 0.23 C, the charging specific capacity is 645 - 655 mAh / g, and the discharging specific capacity is 2.1 - 2.6 mAh / g.
[0033] (2) The present invention improves the rate performance of the modified lithium-ion cathode material by increasing the electronic conductivity of the material and shortening the migration distance of lithium ions. The conductivity (electronic conductivity) is improved by sintering to in-situ grow a layer of carbon material on the surface and in the middle of the modified lithium-ion cathode material. Shortening the migration distance of lithium ions is mainly achieved by controlling the crushing and sintering processes to obtain an agglomerated modified lithium-ion cathode material. The above methods improve the conductivity and ion migration rate of the material. In the charging voltage range of 2.8 - 4.25 V, with a charge-discharge current density of 0.23 C, the charging specific capacity is 645 - 655 mAh / g, and the discharging specific capacity is 2.1 - 2.6 mAh / g. The charging specific capacity is high, the discharging specific capacity is low, and the material quickly deactivates after complete delithiation, thus effectively improving the active lithium consumed during the charge-discharge process of the battery and achieving the improvement of the cycle performance of the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 XRD pattern of the modified lithium-ion cathode material prepared in Example 1;
[0035] Figure 2 SEM image of the modified lithium-ion cathode material prepared in Example 1;
[0036] Figure 3 SEM image of the modified lithium-ion cathode material prepared in Comparative Example 1;
[0037] Figure 4 SEM image of the modified lithium-ion cathode material prepared in Comparative Example 2;
[0038] Figure 5 SEM image of the modified lithium-ion cathode material prepared in Comparative Example 3;
[0039] Figure 6Charge curves of the modified lithium-ion cathode materials prepared in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3. Detailed implementation manners
[0040] The concept of the present invention and the technical effects produced will be clearly and completely described below in conjunction with the embodiments to fully understand the purpose, features, and effects of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative efforts belong to the scope of protection of the present invention.
[0041] Example 1
[0042] The preparation method of the modified lithium-ion cathode material in this example is as follows in specific experimental steps:
[0043] (1) Weigh lithium hydroxide monohydrate and iron oxide according to the molar ratio of Li:Fe of 5.5:1, and then put them into a mixer and mix evenly to obtain a mixed material;
[0044] (2) Under the condition of oxygen, the mixed material obtained in step (1) is subjected to the first sintering. The temperature is raised to 450 °C and held for 4 h, then the temperature is raised to 480 °C and held for 12 h. The heating rate is 5 °C / min, and the cooling procedure is to cool with the furnace to room temperature, and then it is pulverized by a jet mill to obtain fine powder with a particle size D50 of about 2 μm;
[0045] (3) Weigh the fine powder in step (2) and glucose according to a mass ratio of 10:1, mix them, and under nitrogen protection, carry out the second sintering. The temperature is raised to 700 °C and held for 6 h. The heating rate is 5 °C / min, and the cooling procedure is to cool with the furnace to room temperature. Then it is sieved through a 300-mesh sieve to obtain a carbon-doped and coated modified lithium-ion cathode material. The XRD analysis of the phase is as Figure 1 shown, and the morphology is as Figure 2 shown.
[0046] Figure 1 XRD pattern of the carbon-doped and coated modified lithium-ion cathode material prepared in Example 1 of the present invention; from Figure 1 it can be seen that the main phase measured of the material corresponds to the PDF card of Li5FeO4. The peak intensity of lithium carbonate in the material is relatively weak, and the content of the by-product lithium carbonate formed by the reaction of the carbon material and the lithium source is small, indicating that the sample prepared according to the scheme of Example 1 is a relatively pure substance.
[0047] Figure 2It is the SEM image of the carbon-doped and coated modified lithium-ion cathode material prepared in Example 1. It can be seen from the figure that the material mainly exists in the form of aggregates, the particle size of the secondary particles is small, and the surface of the material is uniformly coated with a layer of carbon material. This enables the material to have a higher specific capacity and a lower charging voltage platform under high-rate charging. At the same time, the uniform coating of carbon on the surface of the material also increases the stability of the material in air.
[0048] Example 2
[0049] The preparation method of the modified lithium-ion cathode material in this example is as follows:
[0050] (1) Weigh lithium hydroxide monohydrate and iron oxide according to the molar ratio of Li:Fe of 6.0:1, and then put them into a mixer and mix evenly to obtain a mixed material;
[0051] (2) Under the condition of oxygen, sinter the mixed material obtained in step (1) for the first time. Heat it up to 450 °C and keep it warm for 4 h, then heat it up to 480 °C and keep it warm for 12 h. The heating rate is 5 °C / min, and the cooling procedure is to cool it down to room temperature with the furnace. Grind it with a jet mill to obtain fine powder with a particle size D50 of about 2 μm;
[0052] (3) Weigh the fine powder in step (2) and glucose according to the mass ratio of 10:1, mix them, and under the protection of nitrogen, conduct the second sintering. Heat it up to 700 °C and keep it warm for 6 h. The heating rate is 5 °C / min, and the cooling procedure is to cool it down to room temperature with the furnace. Then pass it through a 300-mesh sieve to obtain the carbon-doped and coated modified lithium-ion cathode material.
[0053] Example 3
[0054] The preparation method of the modified lithium-ion cathode material in this example is as follows:
[0055] (1) Weigh lithium hydroxide monohydrate and iron oxide according to the molar ratio of Li:Fe of 5.8:1, and then put them into a mixer and mix evenly to obtain a mixed material;
[0056] (2) Under the condition of oxygen, sinter the mixed material obtained in step (1) for the first time. Heat it up to 450 °C and keep it warm for 4 h, then heat it up to 480 °C and keep it warm for 12 h. The heating rate is 5 °C / min, and the cooling procedure is to cool it down to room temperature with the furnace. Grind it with a jet mill to obtain fine powder with a particle size D50 of about 2 μm;
[0057] (3) Weigh the fine powder and glucose in step (2) according to a mass ratio of 10:1, mix them, and under nitrogen protection, conduct the second sintering. Heat up to 700 °C, hold for 6 h, with a heating rate of 5 °C / min. The cooling procedure is to cool down to room temperature with the furnace, and then pass through a 300-mesh sieve to obtain the modified lithium-ion cathode material doped and coated with carbon.
[0058] Comparative Example 1
[0059] Compared with Step (1) of Example 1 in Comparative Example 1, the molar ratio of Li:Fe in Step (1) of Example 1 is 7:1.
[0060] The SEM of the modified lithium-ion cathode material obtained by the method of Comparative Example 1 is as Figure 3 shown.
[0061] Comparative Example 2
[0062] Compared with the preparation of the material in Example 1 in Comparative Example 2, the crushing particle size D50 in Step (2) of the example is controlled to be 15 μm.
[0063] The SEM of the modified lithium-ion cathode material obtained by the method of Comparative Example 2 is as Figure 4 shown.
[0064] Comparative Example 3
[0065] Compared with the preparation of the modified lithium-ion cathode material in Example 1 in Comparative Example 3, the sintering temperature in Step (3) of Example 1 is changed to 800 °C and held for 12 h.
[0066] Figure 3 It is the SEM image of the modified lithium-ion cathode material prepared in Comparative Example 1. It can be seen from the figure that the particle size of the material is relatively large, and there is less carbon source on the surface of the material. mainly because too much lithium reacts with the carbon source to generate more lithium carbonate, resulting in a decrease in the specific capacity of the material and adverse situations such as slurry stirring and gelation.
[0067] Figure 4 It is the SEM image of the modified lithium-ion cathode material prepared in Comparative Example 2. Since there is no crushing, after sintering, the particles of the material are relatively large, and the resistance for lithium ions to escape from the interior of the material is large, and the specific capacity of charging is low.
[0068] Figure 5 It is the SEM image of the modified lithium-ion cathode material prepared in Comparative Example 3. Due to the too high second sintering temperature, the particles of the material grow, and the carbon source on the surface of the material becomes carbon dioxide, reducing the carbon content, resulting in a significant decrease in the specific capacity of the material.
[0069] The modified lithium-ion cathode materials, conductive agent SP, binder PVDF, and solvent NMP prepared in Example 1 and Comparative Examples 1-3 were mixed, and the mixture was stirred to obtain a slurry. The slurry was uniformly coated on aluminum foil, dried and sliced. The cut positive electrode sheets, electrolyte, and separator were assembled into coin cells, and the electrochemical performance of the cells was tested after standing. The test reference current density was 1C = 600 mA / g.
[0070] Figure 6 Figure 4 shows the charge specific capacity-voltage curves (the abscissa is the specific capacity and the ordinate is the voltage) of the coin cells for the materials prepared in Example 1 and Comparative Examples 1-3, which also shows that the sample prepared in Example 1 has a low voltage plateau and a high specific capacity.
[0071] The first-cycle test results of the coin half-cells of the modified lithium-ion cathode materials in Example 1 and Comparative Examples 1-3 are shown in Table 1:
[0072] Table 1
[0073]
[0074] Table 1 shows the charge specific capacity of the first cycle of the modified lithium-ion cathode materials in Example 1 and Comparative Examples 1-3. In Example 1, the charge specific capacity measured at a current density of 0.23C at a voltage of 2.8 - 4.25V was 649.74 mAh / g, and the discharge specific capacity was 2.3 mAh / g. This can better improve the cycling performance of lithium-ion batteries, which is superior to Comparative Examples 1-3. The modified lithium-ion battery material is prepared by controlling processes such as lithium doping, sintering, and pulverization to obtain a modified lithium-ion battery cathode material with a stable carbon-containing structure.
[0075] The present invention is not limited to the above embodiments. Within the knowledge scope of those of ordinary skill in the art to which the present invention pertains, various changes can be made without departing from the gist of the present invention. In addition, without conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other.
Claims
1. A modified lithium-ion battery cathode material, characterized in that, The chemical formula of the modified lithium-ion battery cathode material is Li5FeO4@C; the modified lithium-ion battery cathode material is an aggregate, and the aggregate is formed by aggregating spherical particles; The average particle size of the modified lithium-ion battery cathode material is 1.0 - 10 μm, and the specific surface area is 3.0 - 15.0 m 2 / g; The particle size of the spherical particles is 10-500 nm; When the modified lithium-ion battery cathode material is charged and discharged at a current density of 0.23C in the charging voltage range of 2.8-4.25V, the charging specific capacity is 645-655 mAh / g, and the discharging specific capacity is 2.1-2.6 mAh / g; The preparation method of the modified lithium-ion battery cathode material includes the following steps: (1) Mix a lithium source and an iron source, conduct a first sintering, and pulverize to obtain a pulverized material; (2) Mix the pulverized material with a carbon source, conduct a second sintering, pulverize, and screen to obtain the modified lithium-ion battery cathode material; the molar ratio of lithium in the lithium source to iron in the iron source is (5.0-6.0):1; the temperature of the second sintering is 450-750 °C; the particle size D50 of the pulverized material is 1.0-5.0 μm; In step (1), the temperature of the first sintering is 400-480 °C, and the atmosphere of the first sintering is oxygen; In step (2), the carbon source is at least one of polyethylene glycol, polyvinyl alcohol, polyacrylic acid, polypyrrole, fatty alcohol polyoxyethylene, glucose, and sucrose.
2. The modified lithium ion battery cathode material according to claim 1, characterized in that, The mass percentage of carbon in the modified lithium-ion battery cathode material is 1-18%.
3. The preparation method of the modified lithium-ion battery cathode material according to any one of claims 1-2, characterized in that, Including the following steps: (1) Mix a lithium source and an iron source, conduct a first sintering, and pulverize to obtain a pulverized material; (2) Mix the pulverized material with a carbon source, conduct a second sintering, pulverize, and screen to obtain the modified lithium-ion battery cathode material; the molar ratio of lithium in the lithium source to iron in the iron source is (5.0-6.0):1; the temperature of the second sintering is 450-750 °C; the particle size D50 of the pulverized material is 1.0-5.0 μm; In step (1), the temperature of the first sintering is 400-480 °C, and the atmosphere of the first sintering is oxygen; In step (2), the carbon source is at least one of polyethylene glycol, polyvinyl alcohol, polyacrylic acid, polypyrrole, fatty alcohol polyoxyethylene, glucose, and sucrose.
4. The preparation method according to claim 3, characterized in that, In step (1), the lithium source is at least one of lithium hydroxide, lithium carbonate, lithium acetate, lithium borate, lithium metaborate, lithium lactate, lithium nitrate, lithium oxalate, or lithium oxide.
5. The preparation method according to claim 3, characterized in that, In step (1), the iron source is at least one of iron nitrate, ferrous nitrate, ferric chloride, ferrous chloride, ferric sulfate, ferrous sulfate, ferric citrate, iron oxide, or magnetite.
6. The preparation method according to claim 3, wherein In step (1), the heating rate of the first sintering is 1-10 °C / min, and the time of the first sintering is 4-20 h; in step (2), the heating rate of the second sintering is 1-10 °C / min, and the time of the second sintering is 4-12 h.
7. A battery, characterized in that, Including the modified lithium-ion battery cathode material according to any one of claims 1-2.
Citation Information
Patent Citations
Pre-embedding-free lithium-type lithium-ion capacitor and manufacturing method thereof
CN106601489A
Synthesis process of lithium-rich oxide and lithium ion battery containing lithium-rich oxide
CN108878849A
Lithium iron oxide material and preparation method thereof
CN110498449A
Carbon-coated lithium-rich oxide composite material and preparation method thereof
CN111725576A
CARBON-COATED Li5FeO4
JP2019085314A